MENINGKATKAN HASIL BELAJAR PKN PADA MATERI PENGAMBILAN KEPUTUSAN BERSAMA MELALUI METODE BERMAIN PERAN (ROLE PLAYING) SDN. 2 MAKMUR KABUPATEN BIREUEN - Anwar Anwar (Jurnal Ilmiah Peuradeun, 2014)
This study was conducted based on the lack of civic education learning outcomes matter Joint Decision 2 Elementary School in Prosper, as a result of the use of learning methods are still lacking to arouse student interest. This study aims to improve learning outcomes Civics Material Rewarding joint decision on the Student Grade 5 Elementary School 2 Makmur by applying the method of playing a role (Role Playing). This study was conducted with the design of classroom action research (CAR) with a model of the teacher as researcher. The results showed that the application of the method of playing a role in the learning material Civics Appreciating the joint decision to improve learning outcomes Civics in Elementary School fifth grade students 2 Makmur. Improved learning outcomes Civics joint decision Appreciate material is characterized by an increase in the value achieved in the evaluation of learning outcomes in each cycle.